Indoor Dust Exposure Detection System For Air Purifier Controller Based Arduino And LabVIEW - Indah Nursyamsi Handayani; Mamurotun Mamurotun (SANITAS: Jurnal Teknologi dan Seni Kesehatan, 2019)
Dust is a very small solid particle (generally in units of micron) carried by air so it can be breathed anywhere either outdoors or indoors. According to the decision of kepala badan pengendalian dampak lingkungan number: Kep-107/Kabapedal/11/1997, dust exposure is one of the indicators of air pollution affecting the quality of life and public health. Therefore, a system capable of detecting and controlling the level of dust exposure is required. In this study a dust-proof detection was designed using the GP2Y1010AUOF sensor as a dust or particulate matter (PM10) and DS18B20 sensor which is a digital temperature sensor to monitor room temperature. As a simulation of air neutralization used mini car home dual use usb humidifier water-drop air purifier aroma diffus, Arduino Uno as Master Control Unit (MCU) which functions to manage data sensor readings into digital data and to display the level of exposure of dust and air temperature of the room is used LCD character 16x2. A graphical and numerical display of data is displayed on a computer or laptop using graphical user interface LabVIEW.